Prevention and Management of Noncommunicable Disease: The IOC Consensus Statement, Lausanne 2013 - Matheson, G. O.; Klügl, M.; Engebretsen, L.; Bendiksen, F.; Blair, S. N.; Börjesson, M.; Budgett, R.; Derman, W.; Erdener, U.; Ioannidis, J. P. A.; Khan, K. M.; Martinez, R.; et al. (Clinical Journal of Sport Medicine, 2013)
Morbidity and mortality from preventable, noncommunicable chronic disease (NCD) threatens the health of our populations and our economies. The accumulation of vast amounts of scientific knowledge has done little to change this. New and innovative thinking is essential to foster new creative approaches that leverage and integrate evidence through the support of big data, technology, and design thinking. The purpose of this paper is to summarize the results of a consensus meeting on NCD prevention sponsored by the International Olympic Committee (IOC) in April 2013. Within the context of advocacy for multifaceted systems change, the IOC's focus is to create solutions that gain traction within health care systems. The group of participants attending the meeting achieved consensus on a strategy for the prevention and management of chronic disease that includes the following: